Spontaneous or photo-induced resolution of papular elastolytic giant cell granuloma? A case report with considerations on its etiopathogenesis and clinical approach - Andrea Marani; Davide Bertolla; Alessia Caligiure; Anna Rita Lombardi; Andrea Conti (Dermatology Reports)
Papular elastolytic giant cell granuloma (PEGCG) is a rare subtype of elastolytic giant cell granuloma (EGCG), typically presenting as asymptomatic papules in non-photo-exposed areas and lacking annular or photo-distributed lesions. Histologically, it overlaps with other EGCG variants, showing features like elastolysis, elastophagocytosis, and multinucleated giant cell infiltrates. The etiopathogenesis remains unclear, particularly the role of ultraviolet radiation (UV), and its clinical management is not well defined. We report a case of PEGCG that, after a one-year history, achieved complete clinical remission following two and a half months of sun exposure during the summer (heliotherapy). This case offers insights into its etiopathogenesis and clinical management, supported by a review of the existing literature.